2022
DOI: 10.3390/pathogens11030301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sainfoin (Onobrychis viciifolia) Pellets on Parasitological Status, Antibody Responses, and Antioxidant Parameters in Lambs Infected with Haemonchus contortus

Abstract: Our study analyzed the parasitological status, antibody responses, and antioxidant parameters of lambs experimentally infected with a gastrointestinal nematode during the consumption of sainfoin pellets (SFPs) for 14 d. Twenty-four lambs infected with Haemonchus contortus were separated into two groups: untreated animals (control) and animals treated with SFPs (600 g dry matter/d). SFP treatment began on day (D) 30 post-infection. The number of eggs per gram (EPG) of feces was quantified on D18, D23, D26, D30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Ocampo-Gutiérrez et al observed that flavonol and flavonoid derivative compounds such as coumaric acid possess high nematocidal activity and they could be assessed in future studies searching for natural phytocompounds for controlling haemonchosis in small ruminants [ 6 ]. Komáromyová et al studied available dietary antioxidants in the form of sainfoins [ 7 ]. They sustain the antibody response and thus indirectly improve the resistance of the animals against H. contortus.…”
mentioning
confidence: 99%
“…Ocampo-Gutiérrez et al observed that flavonol and flavonoid derivative compounds such as coumaric acid possess high nematocidal activity and they could be assessed in future studies searching for natural phytocompounds for controlling haemonchosis in small ruminants [ 6 ]. Komáromyová et al studied available dietary antioxidants in the form of sainfoins [ 7 ]. They sustain the antibody response and thus indirectly improve the resistance of the animals against H. contortus.…”
mentioning
confidence: 99%